Elite female freestyle wrestlers` competitive performance profiling by technical mastery rating criteria - Tarakanov, B. I.; Apoyko, R. N.; Petrov, S. I.; Vorobyeva, N. V. (Theory and Practice of Physical Culture, 2018)
The study gives a detailed analysis of the elite female wrestlers` competitive performance profiles using the most informative technical mastery rating criteria, for the period of 2006 till now. The fight control variations were profiled versus the changes in rules and levels of competitions and the specific stages in the elite freestyle wrestling development process. The study data and analyses show the need in the competitive performance improvement, extension of the average bout duration and cutting down the time intervals in between the attacks. On the whole, the study data show fast progress of the women freestyle wrestling, with most of the competitive performance rating criteria being fairly close to that in the men freestyle wrestling; and the need for the requirements to the techniques and tactics in the elite women`s freestyle wrestling being stepped up to encourage progress in this sport.